(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
"Teaching of the modern method of GUS teaching" to try in the article "characteristics of communication". to show different approaches to using the method, depending on the teaching depending on the nature of the material and the age group of the students. Application of the method We have made visible the unique features of Armenian literature. based on the analysis of literary works included in the school curriculum on.